2022
DOI: 10.3390/diagnostics12081982
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Salmonella Prosthetic Valve Endocarditis Complicated by Splenic Infarction and Aortic Pseudoaneurysm in a Patient with Double Prosthetic Valves: A Case Report

Abstract: Endocarditis is an extremely rare complication of Salmonellosis with an incidence of 0.2–0.4%. It is a destructive and invasive infection that follows a highly complicated course and carries a high mortality rate that exceeds 45%. Multiple predisposing factors for Salmonella endocarditis have been described in the literature, including human immunodeficiency virus infection, congenital heart diseases, and the presence of a prosthetic valve. Herein, we report a case of Salmonella prosthetic valve endocarditis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The literature review revealed 21 case reports on Salmonella PVE and one case report on Salmonella native valve endocarditis [3,4,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The results of the literature review and our case are summarized in Table 1 and described in more detail in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review revealed 21 case reports on Salmonella PVE and one case report on Salmonella native valve endocarditis [3,4,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The results of the literature review and our case are summarized in Table 1 and described in more detail in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Salmonella is a common cause of enteritis and accounts for approximately 5-10% of cases of bacteremia [1,2]. It is also a rare cause of destructive endocarditis, including prosthetic valve endocarditis (PVE), which occurs in only 0.2-0.4% of cases of salmonellosis [3,4]. PVE has a high mortality rate due to complications such as conduction abnormalities, septic embolism, perforation, valve rupture, and paravalvular abscess (PA) [3,5].…”
Section: Introductionmentioning
confidence: 99%